The Relationship Of Knowledge Of Pregnant Women In Trimester Iii About The Labor Process With The Level Of Anxiety Facing Delivery At The Mandate Clinic - Rizky Andriani Bakara; Desi Anggraini (Science Midwifery, 2020)
The development of physical, mental and social health of mothers and babies needs to be considered. This can cause problems and anxiety for a mother who is in pregnancy, because anxiety is a major component of almost all psychiatric disorders. The research method used isanalytical observationwith a cross sectional approach. The population is all pregnant women in the third trimester at the Manda Clinic, totaling 30 people. The sample technique is a total sampling of 30 respondents. The results of the analysis showed that of the 30 respondents who had less knowledge the majority had severe anxiety levels as many as 5 people (16.6%) and with good knowledge the majority did not have anxiety levels as many as 4 people (13.3%), experiencing mild anxiety levels as many as 3 people (10%) and 2 people (6.7%) experienced severe anxiety. While having sufficient knowledge, the majority experienced moderate anxiety levels as many as 5 people (16.6%), experienced severe anxiety as many as 3 people (10%) and experienced mild anxiety as many as 2 people (6.7%). The results of the chi-square statistical test obtained p = 0.001, This means that there is a relationship between the knowledge of pregnant women in the third trimester about the labor process and the level of anxiety facing childbirth. It is recommended to pregnant women in the third trimester to add insight and seek information about the labor process with the level of anxiety facing childbirth so that mothers can know the labor process and the anxiety that occurs when facing childbirth.